Perceptions of expressed breast milk for preterm infants in Malawian hospitals: A qualitative study. Issue 2 (April 2022) - Ong, Anna-Joy; Woo Kinshella, Mai-Lei; Salimu, Sangwani; Vidler, Marianne; Elango, Rajavel; Banda, Mwai; Dube, Queen; Goldfarb, David; Kawaza, Kondwani; Nyondo-Mipando, Alinane Linda
Abstract: Background: Expressed breastmilk (EBM) can support lactation for mothers of preterm infants with underdeveloped feeding skills. However, there may be implementation challenges in resource-limited global health settings. Objective: To explore EBM barriers and facilitators perceived by caregivers and healthcare workers in Malawi. Methods: A secondary analysis of in-depth interviews exploring breastfeeding support at health facilities conducted at three secondary-level district hospitals and one tertiary-level central hospital in southern Malawi. Interviews underwent content analysis in NVivo 12 (QSR International, Melbourne, Australia). Results: There were 58 healthcare workers and 54 caregivers interviewed. Caregiver unfamiliarity, maternal exhaustion, and inadequate clinical support/equipment were barriers to EBM practice. Caregiver acceptance was supported by witnessing infant growth. Demonstrations of EBM by healthcare workers and family support also facilitated practice. Conclusion: Raising community awareness and extending counselling to family members upon initiation are vital to supporting mothers practice EBM in resource-limited global health settings with chronic staffing shortages.